FINANCIAL LITERACY ANALYSIS OF HOUSEHOLD FINANCIAL BEHAVIOR IN INDONESIA: A LITERATURE REVIEW - Teguh Prakoso; Hajar Mukaromah; Pemy Christiaan (Adiba Aisha Amira, 2024)
Financial literacy plays an important role in shaping the financial behavior of households in Indonesia. Households with higher levels of financial literacy tend to have better financial planning, manage their budgets regularly, and are better prepared for economic shocks. Conversely, households with low financial literacy often experience difficulties in managing finances, get trapped in excessive debt, and lack emergency funds and long-term investments. Efforts to improve the financial literacy of Indonesians have been made through various education and socialization programs by the government, financial institutions, and non-governmental organizations. However, challenges remain in reaching all levels of society, especially in rural areas and low-income groups. Further research is needed to identify effective financial education methods in accordance with the socio-cultural characteristics of the Indonesian people. In addition, strengthening regulations and consumer protection are also needed to create a financial ecosystem that supports increased financial literacy and inclusion. With increased financial literacy, it is expected that households in Indonesia can make wiser financial decisions, improve welfare, and contribute to national economic stability.